Formation mechanism of tourists’ pro-environmental behavior in plateau ecotourism destination - Lulu Wang; Hu Yu; Bin Zhou (Humanities & Social Sciences Communications)
Abstract In response to the scarcity of research on the psychological factors and formation mechanism of tourists’ pro-environmental behavior in plateau ecotourism destinations, this study takes the Shangri-la in Yunnan-Guizhou Plateau as a case, developed an integrated model and tested with structural equation model to obtain accurate and unbiased path coefficients, and jointly exploring the formation mechanism of tourists’ pro-environmental behavior in plateau ecotourism destination. Based on the stimulus-body-response theory and rational behavior theory, this study conducted field investigations and acquired 516 questionnaires. Through analysis, it was discovered that the pro-environment behavior of tourists in plateau ecotourism destinations is influenced by external contextual factors and internal psychological factors. The natural environment and the cultural atmosphere can evoke tourists’ awe, and then awe can directly and positively influence pro-environment behavior, and indirectly influence pro-environment behavior through the dual paths of self-attitude and subjective norms. The conclusion explains the internal logic and action mechanism of tourists’ pro-environment behavior in plateau ecotourism destination, and provides a reference for decision-making in plateau ecotourism destination’s construction and the cracking of tourists’ negative environmental impacts.